List of IMF Member Countries with Delays in Completion of Article IV Consultations or Mandatory Financial Stability Assessments over 18 Months. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
In accordance with Executive Board Decision No. 15106-(12/21), the Fund will publish on its external website a list of member countries whose Article IV consultations or mandatory financial stability assessments have been delayed by more than 18 months, as of the date of publication, since the expected deadline for conclusion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet